A quality model for critical embedded systems - Oliveira, Brauner Roberto do Nascimento (2017)
Embedded systems, including critical embedded systems (CES) are increasingly present in the modern society, providing specific solutions from small to large complex systems, such as in cars, airplanes, and healthcare equipment. Failures in these systems can result in damage to human beings, and to the environment, or can represent an unrecoverable financial loss. In this sense, it is very important to ensure they are built with quality. To provide such quality, it is necessary to consider their software architecture, which impacts on the quality of the systems. This way, the main objective of this Masters project is to propose a quality model concerning the most important quality attributes for CES, which may be used to support (but not limited to) architectural activities such as analysis and evaluation in the context of CES.